Answers

2014-06-08T09:46:05+08:00
Solve (x + 1)(x – 3) = 0.This is a quadratic, and I'm supposed to solve it. I could multiply the left-hand side, simplify to find the coefficients, plug them into the Quadratic Formula, and chug away to the answer.But why would I? I mean, for heaven's sake, this is factorable, and they've already factored it and set it equal to zero for me. While the Quadratic Formula would give me the correct answer, why bother with it? Instead, I'll just solve the factors:(x + 1)(x – 3) = 0 
x + 1 = 0  or  x – 3 = 0 
x = –1  or  x = 3
The solution is  x = –1, 3

0